Gay Group Fighting For SOGIE: Policy Advocacy of The Elimination of Sexual Violence Bill by Gaya Nusantara Organization - Hidayati, Lutfia Nurul; Nurany, Fierda (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2022)
The aim of the research was to discover the importance of the agenda of the gay group in fighting for SOGIE towards the bill draft on the Elimination of Sexual Violence (ESV) through policy advocacy. In Indonesia, LGBTIQ groups remain getting violence and discrimination based on SOGIE. The problem was regarded as fight of the actors in a policy framework from the integrated advocacy theory which said by Roem Topatimasang. Integrated policy advocacy provides an important device for practitioner to make a policy change that was helped by an interested group. This research used a qualitative research method with a descriptive approach. Research location was the Gaya Nusantara foundation. The informant consisted of four informants involved in the advocacy struggles. The result of the research showed that the Gay group incorporated in the Gaya Nusantara foundation in fighting for SOGIE to be included in the specific bill had not produced positive result in favor of them who insisted on the importance they brought.